2020
DOI: 10.3389/fnins.2020.00491
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Model of Radiomics and Satellite Sign Number as Imaging Predictor for Intracranial Hematoma Expansion

Abstract: Background: We aimed to construct and validate a nomogram model based on the combination of radiomic features and satellite sign number for predicting intracerebral hematoma expansion.Methods: A total of 129 patients from two institutions were enrolled in this study. The preprocessed initial CT images were used for radiomic feature extraction. The ANOVA-Kruskal-Wallis test and least absolute shrinkage and selection operator regression were applied to identify candidate radiomic features and construct the Radsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…This method allows us to combine radiomics features into a radiomics signature [31][32][33]. Multi-factor analysis that incorporates individual factors into a factor panel has been widely used in recent studies [34][35][36]. For example, Wang et al [34] constructed an MRI-based radiomics model to predict the muscle-invasive status of bladder cancer and confirmed that the radiomics could be an efficient tool for preoperative prediction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This method allows us to combine radiomics features into a radiomics signature [31][32][33]. Multi-factor analysis that incorporates individual factors into a factor panel has been widely used in recent studies [34][35][36]. For example, Wang et al [34] constructed an MRI-based radiomics model to predict the muscle-invasive status of bladder cancer and confirmed that the radiomics could be an efficient tool for preoperative prediction.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Wang et al [34] constructed an MRI-based radiomics model to predict the muscle-invasive status of bladder cancer and confirmed that the radiomics could be an efficient tool for preoperative prediction. Similarly, Xu et al [35] developed a radiomics nomogram to predict intracerebral hematoma expansion and found that the nomogram could serve as a convenient measurement. Pan et al [36] used the LASSO logistic method to identify optimal radiomics features for preoperative classification of ovarian cystadenoma.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we devised and validated hematoma radiomics signa- Radiomics analysis has been widely applied in oncologic imaging for molecular subtyping, survival prognostication, and prediction of treatment response [8,[21][22][23]. Recent studies suggested that hematoma radiomics features can predict the likelihood of hematoma expansion [24][25][26][27]. In this study, we showed that while hematoma volume and radiomic shape features had strong association with severity of baseline clinical presentation and b R. R. Wilcox percentile bootstrap method for comparing dependent robust correlations [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used for evaluating tumor prognosis, selecting appropriate treatment, and predicting lymph node metastasis [ 7 , 8 ]. Although some researchers have predicted parenchymal hemorrhage enlargement with radiomics technology [ 9 11 ], few have tried to predict IVH growth. In this study, we aimed to develop a model that incorporates clinical and radiomics features to identify patients at high risk for IVH growth in the acute phase of ICH.…”
Section: Introductionmentioning
confidence: 99%